Perlindungan Hukum Bagi Pihak yang Beritikad Baik Dalam Perjanjian Jual Beli (Studi Putusan Nomor 15/pdt.G/2018/PN.Sby) - Syifa Miftahuljannah; Taun Taun (Universitas Batanghari Jambi, 2021)
Buying and selling is a common activity that is carried out in everyday life. The sale and purchase transaction is deemed to have occurred when the parties have reached an agreement on the goods sold and the price offered which is then standardized into an agreement. However, often the making and implementation of agreements does not heed the terms and legal principles contained in the KUHPer which should be used as guidelines both at the time of making and implementing the agreement. One of these cases is contained in Decision Number 15 / pdt.G / 2018 / PN.Sby. This study aims to determine the criteria in determining whether a party has good intentions in carrying out a sale and purchase agreement and legal protection against parties with good intentions. In writing this study using the normative legal method, namely by examining the contents of the decision which is then analyzed by interpretation of the law. Based on the research results, to see that one of the parties has good intentions is in two ways, the first is subjectively or at the time of negotiation and contract preparation and objectively by seeing how he can obey the contents of the contract agreement as long as the agreement is implemented. Legal protection that can be provided is by resolving disputes by making legal suits either through non-litigation through the Consumer Dispute Resolution Agency with all its powers or by litigation by filing a lawsuit through a public court.